Empowering single mothers in Sabah - Salmah Topimin; Noor Fzlinda Fabeil; Lim, Fui Yee Beatrice; Haslinda Hasan (Zes Rokman Resources, 2021)
Life can be challenging for single mothers. They are viewed as the most vulnerable social groups in society who often lack educational attainment, skills and social networks; thus limiting their opportunities to compete in the labour market. Consequently, single mothers struggle to achieve financial independence and to support the well-being of their family. To help single mothers build a better life, it is crucial to provide single mothers with solid institutional support programmes. This paper explores the extent to which the institutional support programmes designed for single mothers are in accordance with the needs and expectation of the single mothers in Sabah. The views obtained from the leaders of the single mother associations show that the support programmes are useful for single mothers; however, the programmes are still inadequate to lift them out of poverty. Suggestions for improvement of the institutional support programmes for single mothers are highlighted.